PENERAPAN MODEL ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR (Jurnal Pendidikan Dasar, 2019)
Abstract: This study aims to improve student learning outcomes by applying the role playing model in the material of plant parts in the fourth grade of elementary school in science learning. In this case the researcher deepens the science learning material in parts of plants by applying the role playing model, where students will play roles as plants or one part of the plant. The method used by researchers is Classroom Action Research (CAR) by doing two cycles using different actions. After doing two actions on learning, learning outcomes and student activities in learning will increase seen from the average test results starting from the first cycle to the second cycle. In the first cycle the overall average score was 47.6, and in the second cycle 76.8. From the data obtained, it can be seen that in each cycle there is an increase. Thus the model used by researchers in science learning material of plant parts is very suitable to improve student learning outcomes in the learning process to be even better. Keyword : Role playing, Learning outcomes, Plant parts